2003
DOI: 10.3928/1081-597x-20030301-03
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Results With the Femtosecond Neodynium-glass Laser in Refractive Surgery

Abstract: PURPOSE: We evaluated four femtosecond laser intrastromal cutting procedures: creation of a corneal flap for laser in situ keratomileusis (LASIK), tunnel and entry cut for intracorneal ring, corneal flap and removable lens for keratomileusis, and intrastromal ablation for myopia and hyperopia. METHODS: A clinical trial using a femtosecond surgical laser (IntraLase Corporation) was performed in partially sighted eyes. Femto-LASIK treatment was performed on 46 eyes up to -14.00 D; 16 patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…In 2003, Ratkay-Traub et al [1] reported that femtosecond laser-assisted laser in situ keratomileuses (FS-LASIK) had many advantages over mechanical microkeratome, including fewer free caps, buttonholes, and irregular flaps. The disadvantages of FS-LASIK, by contrast, included its relatively complicated procedures involving the femtosecond laser used to make the flap Open Access *Correspondence: zhangfj126@126.com and the excimer laser used to perform corneal reshaping.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Ratkay-Traub et al [1] reported that femtosecond laser-assisted laser in situ keratomileuses (FS-LASIK) had many advantages over mechanical microkeratome, including fewer free caps, buttonholes, and irregular flaps. The disadvantages of FS-LASIK, by contrast, included its relatively complicated procedures involving the femtosecond laser used to make the flap Open Access *Correspondence: zhangfj126@126.com and the excimer laser used to perform corneal reshaping.…”
Section: Introductionmentioning
confidence: 99%
“…A CVL vem ganhando destaque ao longo das últimas décadas, devido principalmente ao potencial de resultados melhores, com o advento do excimer laser, (19) do laser de femtossegundo (20) e da avaliação da biomecânica corneana por meio de novos aparelhos (21)(22)(23) . Ainda assim, considerar que há garantia total dos resultados com o uso de aparelhos modernos pode ser considerado uma conclusão perigosa, tanto para os pacientes, quanto, particularmente, para os oftalmologistas.…”
Section: Discussionunclassified
“…Subsequently, the flap is repositioned, covering the laser-treated surface. In the further development of the LASIK technique, the initial cutting of the flap by mechanical blades was substituted with an usp laser process, taking benefit of this fully contactless and sterile flap-cutting method [29,30]. At laser intensities of ≈ 10 11 W/cm 2 the optical breakdown in the corneal tissue is used to generate pronounced cavities on the micrometer scale.…”
Section: Ophthalmologymentioning
confidence: 99%